Multiple Impacted Anterior Teeth - An Unique Case - Monica Charlotte; Solomon; Keerthilatha M Pai; Auswaf Ahsan; Sunitha Carnelio (Wolters Kluwer Medknow Publications, 2004)
Impacted teeth though a fairly common finding is of great diagnostic challenge. It is a known fact that the tooth most frequently impacted is the mandibular third molar. Few other teeth also have the tendency to remain impacted, but least of all the incisors. An unusual case where all the Permanent mandibular anterior teeth are Impacted is reported.